INDONESIA ECONOMIC POLICY PACKAGE VOLUME 5: COULD IMPACT TO THE ECONOMY? - Januar Hertanto; Zuriana Zuriana; Iskandar Ali Alam (University of Sang Bumi Ruwa Jurai, 2017)
This study was conducted to analyze each of the points contained in Economic Policy Package Indonesia Volume V released by the Indonesia Financial Services Authority (FSA) in October, where the economic policy consists of three points with respect to the policy of Islamic banking, the elimination of double taxation on property, real estate sector, and a decrease in income tax. The purpose of economic policy is to drive economic growth in Indonesia using an exploratory qualitative approach, in which the phenomena to be observed will be analyzed based on the theories related including previous studies related. The results of the analysis is the application of banking products and simplification of the opening of the office network to support the advancement of Islamic banking, to achieve high employment and economic growth then the elimination of double taxation for property and real estate sector to encourage the advancement of the sector at a time the country's economy. Meanwhile a lower income tax rate resulted in increased state revenues from taxes. With a series of policies that made the FSA contribution to economic growth, it is clearly seen that the FSA brought significant progress in Indonesia's economic growth.